Antecedents of knowledge management practices: case of Malaysian practitioners - Mohamed Razi, Mohamed Jalaldeen; Mohd Tamrin, Mohd Izzuddin; Ahmad Dahlan, Abdul Rahman; Mohamad Ali, Noor Azian (2017)
In this paper, we investigated the knowledge management (KM) behavior of executives in Malaysia who work in different sectors and involved in Information Technology (IT) related fields. We proposed a conceptual framework based on the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB) to study their intention and involvement in KM initiatives. We introduce six independent variables that represent the social cultural nature of KM as the antecedence of KM intention. These variables are trust, management support, decentralization, IT support, performance expectancy (PE), and effort expectancy (EE). Moreover, the knowledge creation theory (SECI process) is employed to operationalize the instruments for KM intention and KM behavior. For our online questionnaire, 74 executives responded from both private and government-linked organizations. SmartPLS3 was used to run the analysis. The discriminant validity was ensured with the factor loadings, Cronbach’s alpha, composite Reliability (CR) and average variance extracted (AVE) met the fit requirement of above 0.6, 0.7, 0.7, 0.5 respectively. The path analysis confirmed that only IT support, PE of KM, EE of KM out of the seven proposed hypotheses were the significant predictors of KM intention with p-values below 0.05. And the KM intention significantly predicts KM behavior.